Microswimming by oxidation of dibenzylamine. Issue 25 (8th March 2022) - Wittmann, Martin; Heckel, Sandra; Wurl, Felix; Xiao, Zuyao; Gemming, Thomas; Strassner, Thomas; Simmchen, Juliane
Abstract : Photocatalytic BiVO4  microparticles with an inherent asymmetries can actively move by catalysing the oxidation of dibenzylamine. Abstract : Chemiophoretic nano- and micromotors require a constant flow of product molecules to maintain a gradient that enables their propulsion. Apart from a smaller number of redox reactions that have been used, catalytic reactions are the main source of energy with the obvious benefit of making on-board fuel storage obsolete. However, the decomposition of H2 O2 seems to strongly dominate the literature and although motion in H2 O through water splitting is becoming more popular, so far only a few different reactions have been used for propulsion of photocatalytic microswimmers. Here, we investigate the possibility of extending the range of possible fuelling reactions to organic reactions with high significance in organic synthesis – the oxidation of amines to imines. Herein, motion of the microswimmers is analysed at different amine concentrations and light intensities. The findings thereof are correlated with the reaction products identified and quantified by gas chromatography (GC).